2011
DOI: 10.1111/j.1365-313x.2011.04582.x
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ‐based analysis of changes in the cassava root proteome reveals pathways associated with post‐harvest physiological deterioration

Abstract: SUMMARYThe short storage life of harvested cassava roots is an important constraint that limits the full potential of cassava as a commercial food crop in developing countries. We investigated the molecular changes during physiological deterioration of cassava root after harvesting using isobaric tags for relative and absolute quantification (iTRAQ) of proteins in soluble and non-soluble fractions prepared during a 96 h post-harvest time course. Combining bioinformatic approaches to reduce information redundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 75 publications
4
100
0
Order By: Relevance
“…Similarly, the level of glutathione dehydrogenase was significantly reduced 24 h after harvest. While the increase of APX abundance does not correlate with increased APX activities during early PPD progression (Owiti et al, 2011) (Supplemental Figure 3), our study also revealed that levels of enzymes involved in the reduction of ascorbate and dehydroascorbate are not significantly upregulated.…”
Section: Protein Categories Overrepresentationsupporting
confidence: 48%
See 2 more Smart Citations
“…Similarly, the level of glutathione dehydrogenase was significantly reduced 24 h after harvest. While the increase of APX abundance does not correlate with increased APX activities during early PPD progression (Owiti et al, 2011) (Supplemental Figure 3), our study also revealed that levels of enzymes involved in the reduction of ascorbate and dehydroascorbate are not significantly upregulated.…”
Section: Protein Categories Overrepresentationsupporting
confidence: 48%
“…Previously, we used detergent to extend proteome analysis to the nonsoluble protein fraction of cassava roots (Owiti et al, 2011), which substantially increased proteome coverage. Here, we used SDS to extract total protein from cassava roots during PPD progression.…”
Section: Proteomics Workflow For the Identification Of Cassava Root Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Considered a complex enzymatic process, PPD (Owiti et al, 2011) begins 15 min after the root cutting, and becomes visible between 24 and 72 hours after harvest, rendering roots inappropriate for consumption (Sánchez et al, 2006;Reilly et al, 2007;Morante et al, 2010). The main symptoms of PPD include vascular streaking, which is a blue-black discoloration of the xylem parenchyma, followed by general discoloration of the parenchyma, forming vascular ridges (Reilly et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…4 The iTRAQ approach, specifically, has been adapted to compare and quantify proteins in various plant species. [5][6][7][8][9][10] Digested peptides in each protein sample are labeled with different iTRAQ reagents and samples are then pooled. Therefore, samples can be analyzed by LC/MS at the same time.…”
Section: Introductionmentioning
confidence: 99%